Phraseologisms with the component ворота, вароты, 门/大门 and дверь, дзверы, 门/户/门户 as a part of architectural code of culture - Protasenya, Nina S. (Journal of the Belarusian State University. Philology, 2025)
The article presents results of linguocultural units analysis, implementing the architectural code of culture in the Russian, Belarusian and Chinese languages. The material for the study is based on phraseological units with the ворота, вароты, 门/大门 and дверь, дзверы, 门/户/门户 components, extracted from twelve phraseological dictionaries. An author proposes classification of phraseological units, where they are grouped basing on semantic features that go back to the ontological qualities of gates (doors). Within the framework of the units phraseological group study typological similarities and differences in the implementation of the architectural code in three linguistic cultures have been identified.